Blue's Clues and you - Fruchter , Jason; Nickelodeo (Chicago, Illinois Phoenix International Publications Inc, 2021)
Features Blue and Josh from Blue's Clues in look and find activities
Hobbies
Keywords: Activity books; Picture puzzles